Transferência de controle da resposta de observação diferencial ecóica na tarefa MTS para relações emergentes de tato - Chereguini, Paulo Augusto Costa (Universidade Federal de São Carlos, 2014)
In our lab, for over two decades we have designed and carried out studies that regard teaching and control of basic emerging verbal behavior. Functional independence of tact and mand, as well as responding as listener and speaker are some examples of research aims that caught our attention in the past eight years. In this context, the three articles presented here are a result of seven studies carried out as part of a doctoral research (article 1: studies 1 and 2; article 2: studies 3 to 5; article 3, studies 6 and 7) and feature the history of an experimental pursuit of variables that may account for the establishment of the listenerspeaker bidirectional relation. All three articles investigate the effects of echoic responding in MTS tasks that teach listener behavior and test the emergence of tact. Studies 1 through 5 (articles 1 and 2) carried out with adult participants set an investigative and preparatory condition for the following studies carried out with children with autism and with typical development who present poor verbal repertory. Article 1 aimed to compare the effects of traditional MTS procedures with a modified procedure that adds an echoic differential observing response (DOR) to auditory model stimuli when teaching listener relations and testing the emergence of tact. In article 2 we aimed to extend the analysis of the second procedure s effect when teaching other conditional relations. The analysis of results in articles 1 and 2 was parsimonious, but directed to methodological and conceptual aspects for considering that participants were adults that already presented naming. Article 3 accounts for the most careful product of the current study, however it does not provide conclusive results. General results show that adding a echoic DOR of in the MTS task have not assured but produced superior effects compared to traditional MTS tasks when teaching auditory‐visual relations and testing the emergence of tact and other derived discriminations. Careful analyses on methodological gaps and controlling variables of the teaching procedure are, possibly, the most precious information provided in all three articles. Replications are required and suggested with details as means to make progress in the central research problem that regards the emergence of basic verbal relations.
Transference of control from echoic observing differential responses in MTS tasks to tact emerging relations
Keywords: Comportamento verbal; Tato; Comportamento de ouvinte; Autismo; Tact; Listener behavior; Echoic; Autism; Emerging relations; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO::EDUCACAO ESPECIAL